National pastimes : cinema, sports, and nation - Bonzel, Katharina (Sports, media, and society., 2020)
Katharina Bonzel unravels the delicate matrix of national identity, sports, and emotion through the lens of popular sports films in comparative national contexts, demonstrating in the process how popular culture provides a powerful vehicle for the development and maintenance of identities of place across a range of national cinemas. As films reflect the ways in which myths of nation and national belonging change over time, they are implicated in important historical moments, from Cold War America to the class dynamics of 1980s Thatcherite Britain to the fragmented sense of nation in post-unification Germany. Bonzel shows how sports films provide a means for renegotiating the boundaries of national identity in an accessible, engaging form. National Pastimes opens up new ways of understanding how films appeal to the emotions, using myth-like constructions of the past to cultivate spectators' engagement with historical events.